SUSTAINABILITY OF INVESTMENT OBJECTIVES OF VILLAGE TOURISM ON ORIGINAL INCOME OF VILLAGE (PAD) IN INDONESIA - Subekti; Pangestika, Mirza Anindya (STIE Kusuma Negara, 2020)
Village funds are a new hope for village communities to develop their potential. However, forced planning does not in detail see what exactly is needed by the community makes the village funds do not function optimally. Most of it is only for infrastructure development and only a small portion for sustainable productive activities. Village funds were poured into Village-Owned Enterprises (VOE) by opening village tourism destinations. The ignorance of the village government and the VOE management manage the potential tourism destinations of each region resulting in village tourism destinations being built almost the same in all villages in Indonesia without looking at the backward relations and future relationships of the concept of tourist destinations. This research method uses extraction from the United Nations Conference on Trade and Development (UNCTAD), SWOT Analysis with the Travel and Tourism Competitive Index as a measure of the sustainability of investments, how big is the effect on the original income of the village. The results show that investments made by the village government through VOE are inversely proportional to the village's original income. This study found the concept of novelty to balance investment with genuine village income called Competitiveness Financial Services